Pola Asimetris pada Façade Bangunan-bangunan Baru Bertema Art Deco di Kota Bandung - Saryanto . (FSRD ITENAS, 2011)
Abstract Bandung is one of the city which have many historical-buildings in Indonesia. Some of them still functioned as they were built and other has changed their function and even nearly vanished. Called as “Paris Van Java” makes Bandung become interesting city to be visited every weekend..This situation which make big change and cause the past popular themes of Bandung architecture reappears in a new faces. Many of Art Deco building being renovated and new building which adopt this theme to various need; office, bank, restaurants and even house. But, unique phenomenon have happened is many of Art Deco is not built up fully adopt method of aesthetics of Art Deco itself. So that many from new building have differences form with this themes. Symmetrical Façade in the early a period of growth of Art Deco era will no longger become references of form. A complex problems of towns and also growth of minimalis design trend, causing many of a new Art Deco façade a-symmetrical appearances today Keywords: Art Deco, Bandung, a-symmetrical Abstrak Bandung adalah salah satu kota besar di Indonesia yang mempunyai banyak bangunan besejarah. Beberapa di antara mereka masih berfungsi seperti pertama dibangun dan lainnya telah berubah fungsi, bahkan sebagian telah mendekati punah. Dijuluki